Are the Grandparents Alright?: The Health Consequences of Grandparental Childcare Provision - Peter Eibich; Xianhua Zai (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2022)
This paper examines the causal effect of childcare provision on grandparents' health in the US. We propose the sex ratio among older adults' children as a novel instrument for grandparental childcare provision. Our instrument is rooted in the demographic literature on grandparenthood and exploits that parents of daughters transition to grandparenthood earlier and invest more in their grandchildren than parents of sons. We estimate 2SLS regressions using data from the Health and Retirement Study. The results suggest that childcare provision is not beneficial for grandparents' health and may even be detrimental for physical functioning and subjective health. Specically, grandparenting worsens functional limitations of IADL by 26 percent and subjective health by 9.5 percent.
Keywords: I10; J13; J14; C26; 330; Grandparents; Childcare provision; Instrumental variables; Health